Panduan Praktis untuk Meningkatkan Kinerja Keuangan UMKM: Implementasi Sistem Akuntansi Microsoft Access pada Lamoela Bar untuk Optimalisasi Laporan Keuangan - Ramadana, Mariska; Nadila, Nadila (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The financial management application implemented for Lamoela Bar has brought innovation in the management of micro, small, and medium-sized businesses (MSMEs) in the handicraft industry. With an initial focus on security through a login menu, the app provides restricted access to authorized users. Various app menus, including transaction types, sales, cash transactions, and general ledger, offer easy navigation and business activity recording. The transaction types allow recording of various transaction categories, while the sales menu facilitates efficient product sales recording. The cash transaction menu provides real-time monitoring of cash flow, and the general ledger helps organize transaction records into a ledger. With an intuitive design, this app not only provides efficiency in management but also offers an accurate overview of Lamoela Bar's financial performance. It is expected that the implementation of this app will increase productivity and support sustainable growth for this MSME in the dynamic business world.